Assessment of the Economic Profitability of Fattening Selected Chicken Genotypes in an Organic Farm - Kazimierz Obremski; Józef Tyburski; Paweł Wojtacha; Ewa Sosnówka-Czajka; Iwona Skomorucha; Janusz Pomianowski; Paweł Parowicz (Agriculture, 2023)
The aim of this study was to evaluate whether production costs can be reduced and whether the profitability of organic chicken fattening can be increased by selecting the appropriate genotypes. Rhode Island Red (K-11) and Sussex (S-66) conservative chicken genotypes, as well as modern chicken genotypes such as slow-growing Hubbard JA 957 hybrids and fast-growing Ross 308 hybrids, were selected for the study. One hundred and sixty chickens were used in the experiment (forty birds per group). The birds were fed commercial organic complete feed up to 52 days of age and organic farm-made feed (to reduce costs) between 53 and 81 days of age. Population distribution was determined using the Kolmogorov–Smirnov test. The results were analyzed statistically using one-way analysis of variance (ANOVA) with multiple comparisons and the post hoc Tukey test at a significance level of p < 0.05. The 81-day fattening period (the minimum recommended period in organic farming) led to considerable weight deficits in Rhode Island Red and S-66 chickens and excessive slaughter/trade weights in Hubbard JA 957 and Ross 308 chickens. The feed conversion ratio was high in Rhode Island Red (K-11) and Sussex (S-66) chickens at 4.19 and 4.50, respectively, and much lower in Hubbard JA 957 and Ross 308 chickens at 2.79 and 2.53, respectively. The choice of chicken genotypes had a major impact on the profitability of organic farming, and the total costs of feed and other ingredients per kg of body weight were determined at EUR 3.83 for Rhode Island Red (K-11), EUR 3.90 for Sussex (S-66), EUR 6.57 for Hubbard JA 957, and EUR 6.62 for Ross 308 genotypes. The profitability of organic farming can be increased by selecting modern, meat-type, slow-growing chicken genotypes.